On a record of the ambicoloured Engyprosopon valderostratus (Alcock) (Pisces: Bothidae) off Madras, India - T. Venkateswarlu (Acta Ichthyologica et Piscatoria, 1981)
The author describes a rare ease of ambicolouration on the do called “blind side” of a bothid fish Engyprosopon valderostratus (Alcock) caught off Madras.